Analysis of Outcomes in COVID-19 Patients With Varying Degrees of Hyperlipasemia. Issue 9 (3rd October 2021) - Benias, Petros C.; Inamdar, Sumant; Wee, Diana; Liu, Yan; Buscaglia, Jonathan M.; Satapathy, Sanjaya K.; Trindade, Arvind J.; ,
Abstract : Objectives: Coronavirus disease 2019 (COVID-19) patients may have varying degrees of hyperlipasemia. The aim was to compare outcomes among different levels of hyperlipasemia in patients with COVID-19. Methods: This is a retrospective study examining outcomes among hospitalized COVID-19 patients with a lipase <3× upper limit of normal (ULN), asymptomatic hyperlipasemia (>3× ULN), secondary pancreatitis (typical respiratory COVID-19 symptoms and found to have pancreatitis), and primary pancreatitis (presenting with pancreatitis). Results: Of 11, 883 patients admitted with COVID-19, 1560 patients were included: 1155 patients had normal serum lipase (control group), 270 had elevated lipase <3× ULN, 46 patients had asymptomatic hyperlipasemia with lipase >3× ULN, 57 patients had secondary pancreatitis, and 32 patients had primary pancreatitis. On adjusted multivariate analysis, the elevated lipase <3× ULN and asymptomatic hyperlipasemia groups had worse outcomes with higher mortality (odds ratio [OR], 1.6 [95% confidence interval [CI], 1.2–2.2) and 1.1 [95% CI, 0.5–2.3], respectively), higher need for mechanical ventilation (OR, 2.8 [95% CI, 1.2–2.1] and 2.8 [95% CI, 1.5–5.2], respectively), and longer length of stay (OR, 1.5 [95% CI, 1.1–2.0] and 3.16 [95% CI, 1.5–6.5], respectively). Conclusions: Patients with COVID-19 with elevated lipase <3× ULN and asymptomatic hyperlipasemia have generally worse outcomes than those with pancreatitis.